On the Solutions of a General System of Difference Equations. (17th April 2012) - Elsayed, E. M.; El-Dessoky, M. M.; Alotaibi, Abdullah
Abstract : We deal with the solutions of the systems of the difference equations x n + 1 = 1 / x n - p y n - p, y n + 1 = x n - p y n - p / x n - q y n - q, and x n + 1 = 1 / x n - p y n - p z n - p, y n + 1 = x n - p y n - p z n - p / x n - q y n - q z n - q, z n + 1 = x n - q y n - q z n - q / x n - r y n - r z n - r, with a nonzero real numbers initial conditions. Also, the periodicity of the general system of k variables will be considered.